Lost in translation. Cosa prendere (e cosa lasciare) del dibattito americano su diritto e neuroscienze (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
Recently, the scientific debate on the relationship between law and cognitive neurosciences has sensibly developed, so much that some argues about the necessity to consider this relationship as a new field of legal disciplines. Several are the issues that should be taken into account, such as the value of neuroscientific opinions and reports within the legal proceeding or the evolution of the concept of legal competence. From a philosophical viewpoint, these new scientific developments call for a re?evaluation of the concept of legal personhood and for a reconsideration of traditional concepts, such as the notion of free will. The aim of the paper is to address the main issues that the “new” relationship between law and neurosciences is raising, offering some possible solution for the integration of neuroscientific concepts in the legal discourse.
Keywords: cognitive neuroscience; legal culture; legal philosophy; scientific evidence in legal proceedings; neuroimaging.